Precise U-Pb ages for the cogenetic alkaline Mount LaTour and peraluminous Mount Elizabeth granites of the South Nepisiguit River Plutonic Suite, northern New Brunswick, Canada - Azadbakht, Zeinab; McFarlane, Christopher; Lentz, David (Atlantic Geology)

(untitled) (Atlantic Geoscience Society, 2016)
ABSTRACT The South Nepisiguit River Plutonic Suite consists of various phases of felsic to mafic plutonic rocks of early Devonian age in northern New Brunswick. The felsic portion of this intrusive suite includes a large pluton of homogeneous, peraluminous biotite granite (the Mount Elizabeth Granite), which is flanked on its western side by the alkaline Mount LaTour Granite. New in situ and mineral separate U-Pb Laser Ablation-Inductively Coupled Plasma Mass Spectrometry analyses of monazite and zircon grains from both sides of the suite define a crystallization age of 417.3 ± 0.96 Ma for the Mount Elizabeth Granite and 417.7 ± 4.4 Ma for the Mount LaTour Granite. The new data confirm previous geochronological work and indicate a close temporal relationship between these felsic phases of this plutonic suite.